Spatiotemporal variables to understand visitor travel patterns: A management-centric approach. (September 2020) - Peterson, Brian A.; Brownlee, Matthew T.J.; Hallo, Jeffrey C.; Beeco, J. Adam; White, David L.; Sharp, Ryan L.; Cribbs, Tyler W.
Abstract: Managers of parks and protected areas can use information about visitor travel patterns to conserve the biophysical resource and provide opportunities for quality visitor experiences. Visitor travel patterns are affected by the unique context of each park and protected area and can be assessed in a multitude of ways. Consequently, researchers have used numerous operationalizations and associated methods to understand visitor travel. However, during previous investigations, management input has not been fully taken into consideration to identify which spatiotemporal variables are the most important for understanding visitor travel patterns. In this study, the research team conducted semi-structured interviews and surveyed managers at Theodore Roosevelt National Park to determine which spatiotemporal variables were deemed the most important for understanding visitor travel patterns at the park, and distributed GPS data loggers to day visitors. Next, the spatiotemporal variables identified by managers were used to cluster travel groups using data collected by the GPS data loggers. Travel attributes of these groups were compared to gain more understanding of visitor travel patterns. Lastly, 3D geovisualizations that are intuitive and easy to understand were created for management purposes. A significant finding produced by this research was that managers at Theodore Roosevelt National Park identified three temporal variables as being the most important for understanding visitor travel patterns: total time spent at attraction areas, total time spent at the visitor center, and total time spent in the park.